Perubahan Peran Seni Pada Masyarakat Bali - Djajaprawira, Hermin (STBA Yapari-ABA Bandung, 2011)
Art will constantly evolve in term of its function as time passes. The same goes with the art in Bali, with regard to Barong Keris dance in particular. To Balinese people, Barong Keris dance is an expression of beauty and religious values are considered to be inherent. In Bali economic development can go in harmony with cultural development. Tourism, as it has gone through its spiral process, has helped thrusting creativity in art creation. That is because the people of Bali are able to accomodate the incoming foreign culture.